THE DESIGN PRINCIPLES AND CREATIVITY TOUCH IN JAPANESE GARDENS - Wishnu Aji, Artbanu (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2008)
Japanese gardens have much variety of forms; however their identity can be recognized by viewer as Japanese when they see it. All designers of Japanese garden have to follow design principles of garden making which guide their sense creativity into sense of Japanese spirit. This article will focus on variety of forms of famous Japanese gardens and how their designer develops their creativity in shaping natural landscape into man-madeenvironment.Keywords : design principles, variety, creativity